Effect of Robusta coffee extract gel on fibroblast and collagen during proliferative phase of IIB degree-burn on Long Evans rats - Ulfa Elfiah; Muhammad Fahmi Naufal; Mochammad Amrun Hidayat (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2022)
IIB Degree-burn takes longer to heal because only a small epithelium component remains. It requires a topical agent that can accelerate the wound healing process. One of the wound healing signs is the increased collagen formation as an extracellular matrix produced by fibroblast in the proliferative phase. This study aimed to prove the effect of Robusta coffee extract gel as a topical agent on increasing the number of fibroblasts and collagen density in IIB degree-burn treatment on Long Evans rats. This study used 24 Long Evans rats which were divided into three groups, namely positive control (silver sulfadiazine), negative control (gel base), and treatment group (2.5% of Robusta coffee extract gel). The results showed a higher number of fibroblast (p<0.05) and a denser collagen density (p<0.05) of the Robusta coffee extract gel compared to the control group on day 8 and day 14. These results indicated that the number of fibroblasts and collagen increases that can scavenge free radicals and stimulate the release of cytokines that play a role in increasing fibroblast proliferation. Robusta coffee affects expanding the number of fibroblasts and collagen density to be an alternative topical agent of second-degree burns treatment.